Global trends in novel stable isotopes in basalts: Theory and observations. (1st February 2022) - Soderman, Caroline R.; Shorttle, Oliver; Matthews, Simon; Williams, Helen M.
Abstract: The geochemistry of global mantle melts suggests that both mid-ocean ridge basalts (MORB) and ocean island basalts (OIB) sample lithological and temperature heterogeneities originating in both the upper and lower mantle. Recently, non-traditional stable isotopes have been suggested as a new tool to complement existing tracers of mantle heterogeneity (e.g., major and trace elements, radiogenic isotopes), because mineral- and redox-specific equilibrium stable isotope fractionation effects can link the stable isotope ratios of melts to their source mineralogy and melting degree. Here, we investigate five stable isotope systems (Mg-Ca-Fe-V-Cr) that have shown promise in models or natural samples as tracers of mantle temperature and/or lithological heterogeneity. We use a quantitative model, combining thermodynamically self-consistent mantle melting and equilibrium isotope fractionation models, to explore the behaviour of the isotope ratios of these elements during melting of three mantle lithologies (peridotite, and silica-excess and silica-deficient pyroxenites), responding to changes in mantle mineralogy, oxygen fugacity, temperature and pressure. We find that, given current analytical precision, the stable isotope systems examined here are not predicted to be sensitive to mantle potential temperature variations through equilibrium isotope fractionation processes. By contrast, source lithological heterogeneity is predicted to be detectable in some cases in the stable isotope ratios of erupted basalts, although generally only at proportions of > 10% MORB-like pyroxenite in the mantle source, given current analytical precision. Magnesium and Ca stable isotopes show most sensitivity to a garnet-bearing source lithology, and Fe and Cr stable isotopes are potentially sensitive to the presence of MORB-like pyroxenite in the mantle source, although the behaviour of Cr isotopes is comparatively under-constrained and requires further work to be applied with confidence to mantle melts. When comparing the magnitude and direction of predicted equilibrium isotopic fractionation of peridotite and pyroxenite melts to natural MORB and OIB data, we find that aspects of the natural data (including the mean Mg-Ca-Fe-V isotopic composition of MORB, the range of Mg-Ca isotopic compositions seen in MORB data, the mean Mg-Ca-Cr isotopic composition of OIB, and the range of Mg-V-Cr isotopic compositions in OIB data) can be matched by equilibrium isotope fractionation during partial melting of peridotite and pyroxenite sources – with pyroxenite required even for some MORB data. However, even when considering analytical uncertainty on natural sample measurements, the range in stable isotope compositions seen across the global MORB and OIB datasets suggests that kinetic isotope fractionation, or processes modifying the isotopic composition of recycled crustal material such that it is distinct from MORB, may be required to explain all the natural data. We conclude that the five stable isotope systems considered here have potential to be powerful complementary tracers to other geochemical tracers of the source lithology of erupted basalts. However, continued improvements in analytical precision in conjunction with experimental and theoretical predictions of isotopic fractionation between mantle minerals and melts are required before these novel stable isotopes can be unambiguously used to understand source heterogeneity in erupted basalts.